Low Job Satisfaction and Its Impact on Employee Performance in Fallujah (Awqaf) - Aliwy, Hamid Subhi (Universitas Muhammadiyah Sidoarjo, 2025)
This study tried to discover the impact of motivation on job satisfaction and performance in addition to studying the relationship between job satisfaction and performance in the Fallujah Sunni Endowment Directorate (2025). The researcher created a survey based on existing studies to measure motivation, job satisfaction, and performance, using a 41-question form that includes 18 questions about motivation, 15 about job satisfaction, and 8 about performance. They randomly selected 225 employees from middle and upper management to participate. The study instrument was distributed in the main location in Fallujah, where 150 questionnaires suitable for analysis with SPSS software were recovered in less than 3 months. The findings provided valuable insights for religious management in Iraq, offering practical recommendations for improving motivational strategies and techniques in addition to job satisfaction practices to enhance performance. The study also seeks to contribute to the existing body of knowledge on the interplay between job satisfaction, performance, and motivation in developing organizations, particularly within the context of the Iraqi systems. Highlights: Highlights the positive correlation between motivation, job satisfaction, and performance. Fills a research gap in Iraq’s religious administrative institutions. Offers practical HR strategies for improving organizational outcomes. Keywords: Motivation, Job Satisfaction, Performance